Reliability evaluation of demand-based warm standby systems with capacity storage - Jia, Heping; Peng, Rui; Yang, Li; Wu, Tianyi; Liu, Dunnan; Li, Yanbin (Reliability engineering & system safety, 2022)
•Demand-based warm standby systems with capacity storage are modeled.•Different utilization sequences of warm standby and stored capacity are considered.•Multi-valued decision diagram is proposed for system reliability evaluation.•Chronological characteristics of warm standby activation are embedded.•The method allows systems with arbitrary time-to-failure distributions. Warm standby is an energy-saving redundancy technique that consumes less energy than a conventional hot standby method. It can be naturally integrated with an energy storage technique to enhance system reliability. However, the integration approach of both techniques and the advantage it affords to system reliability have not been reported in literature. This study resolves this limitation by formulating a novel reliability model for demand-based warm standby systems with capacity storage. In this model, the chronological characteristics of warm standby components are explicitly explored before and after their activation. Moreover, different utilization sequences of warm standby components and storage components are embedded to analyze the effects of these sequences on system reliability. A multi-valued decision diagram is developed to evaluate system reliability considering successful activation probabilities of warm standby components. This diagram is applicable to arbitrary component lifetime distributions and warm standby systems. Numerical examples are presented to verify the application of the proposed methodology.